CD226 Attenuates Treg Proliferation via Akt and Erk Signaling in an EAE Model - Wang, Ning; Yi, Hongyu; Fang, Liang; Jin, Jingyi; Ma, Qianli; Shen, Yuting; Li, Juan; Liang, Shuang; Xiong, Jie; Li, Zhuo; Zeng, Hanyu; Jiang, Fengliang; et al. (Frontiers in Immunology, 2020)
Cluster of differentiation 226 (CD226) molecules play a crucial role in the activation of effector CD4+ T cells during the immune response process, but a cell-intrinsic function of CD226 in CD4+ T subsets is not clear. In this study, we showed that Cd226-/- mice were resistant to myelin oligodendrocyte glycoprotein peptide 35-55 (MOG35-55)-induced experimental autoimmune encephalomyelitis (EAE) with highly expressed IL-10+CD4+ T cells and downregulated IL-17A+CD4+ T cells when compared with wild-type (WT) mice. Th17 cell infiltration into the central nervous system (CNS) was largely decreased in the absence of CD226 during EAE. CD226 deficiency facilitated the proliferation of regulatory T cells (Tregs), with increased numbers of Tregs observed in EAE mice, and supported the elevated induced regulatory T cell (iTregs) proliferation in vitro. The Akt and Erk signalling pathways were shown to be involved in Cd226-/- Treg proliferation and function in vivo and in vitro. These findings collectively indicate that CD226 is a key molecule regulating the Treg-mediated suppression of autoimmune responses by inhibiting Treg proliferation. Thus, the results of this study identify additional mechanisms by which CD226 regulates Treg functions in EAE and supports the potential therapeutic effects of anti-CD226 molecules on autoimmune diseases.